The Role of the Apelin/APJ System in the Regulation of Liver Disease - Lv, Xinrui; Kong, Jing; Chen, Wei-Dong; Wang, Yan-Dong (Frontiers in Pharmacology, 2017)
Apelin is an endogenous peptide that is a ligand for the APJ receptor (angiotensin II receptor like-1, AT-1). The apelin/APJ system is distributed in diverse periphery organ tissues. It has been shown that the apelin/APJ system plays various roles in physiology and pathophysiology of many organs. It regulates cardiovascular development or cardiac disease, glycometabolism and fat metabolism as well as metabolic disease. The apelin/APJ system participates in various cell activities such as proliferation, migration, apoptosis or inflammation. However, apelin/APJ function in the liver is still under investigation. In the liver, the apelin-APJ system could play an inhibitory role in liver regeneration and promote Fas-induced apoptosis. It may participate in the formation of hepatic fibrosis or cirrhosis, and even cancer. In this review, we summarize the role of the apelin/APJ system in liver disease.